2020
DOI: 10.1007/s42452-020-2286-2
|View full text |Cite
|
Sign up to set email alerts
|

Implications of biofouling on cross-flow turbine performance

Abstract: While biofouling is known to degrade the performance of marine energy conversion systems, prior experimental work has not explored this topic for cross-flow turbines. Here, we present experiments that investigate the impact of biofouling on turbine power output and structural loads. Using additive manufacturing, a three-dimensional scan of a barnacle was patterned onto the surface of turbine blades at three sizes and number densities, representing the progression from initial colonization to maturity. The impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Overall DKP 18 exhibited the broadest spectrum of activity against the macrofouling organisms screened, also inhibiting cyprid settlement by up to 50% at 0.5 μg/mL; an inhibition value lower than that of many reported antifouling natural products, and at levels comparable to the market antifoulant SeaNine™. 45,76,78 Trends within the linear alkyl substituted DKP series (7)(8)(9)(10)(11) were found to be better defined than the poly-aromatic substituted DKPs (Table 1). DKPs 7 (N α -butyl) and 8 (N α -hexyl) were demonstrated to be inactive (>20 μg/mL), whereas DKPs 9 (N α -octyl, 0.54±0.1 μg/mL) and 10 (N α -decyl, 1.90±0.4 μg/mL) showed good activity against C. savignyi.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall DKP 18 exhibited the broadest spectrum of activity against the macrofouling organisms screened, also inhibiting cyprid settlement by up to 50% at 0.5 μg/mL; an inhibition value lower than that of many reported antifouling natural products, and at levels comparable to the market antifoulant SeaNine™. 45,76,78 Trends within the linear alkyl substituted DKP series (7)(8)(9)(10)(11) were found to be better defined than the poly-aromatic substituted DKPs (Table 1). DKPs 7 (N α -butyl) and 8 (N α -hexyl) were demonstrated to be inactive (>20 μg/mL), whereas DKPs 9 (N α -octyl, 0.54±0.1 μg/mL) and 10 (N α -decyl, 1.90±0.4 μg/mL) showed good activity against C. savignyi.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…7 For example, light calcareous biofouling decreases the power coefficient of cross-flow turbines by up to 15%, while heavier fouling can render turbines incapable of producing power. 8 Biofouling increases green-house gas emissions of ships by up to 40% due hydrodynamic drag 2,9,10 and is increasingly recognised as a primary means for global spread of invasive marine organisms. 11,12 Current estimates place the combined cost of these diverse impacts of marine biofouling at approximately US$60 billion per annum.…”
Section: Introductionmentioning
confidence: 99%
“…Even biofilms as thin as 0.1 mm have been shown to increase skin friction on flat plates [56], while the barnacle heights can exceed 10 mm [57]. Barnacles at such size would cause local flow separation on the turbine blades and thus affect lift and drag components, and even lead to dynamic stall [49].…”
Section: Marine Biofoulingmentioning
confidence: 99%
“…Investigations on the impact of fouling on a 1:5 scale cross-flow turbine with a model diameter of 172 mm showed that the impact of fouling on power output is substantial and, for the most severe cases, corresponding to k/c = 0.035, a 100% power reduction was found, while only a minimal reduction in thrust was measured [5]. Walker et al investigated the effect of fouling on a 800mm horizontal axis turbine (at 1:25 scale), using model scale testing, as well as predicting the turbines performance using a blade element momentum model (BEM) informed by wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%